Memorias de El Prado : arquitectura y urbanismo 1920-1960 - Ferro Bayona, Jesús, 1943-; Llanos Díaz, Rossana; Ángel Ángel, Oscar; Badillo Jiménez, Walberto; Iglesias Bermúdez, Rafael; Pérgolis, Juan Carlos, 1943-; Villalón Donoso, Jorge (Área metropolitana de Barranquilla (Colombia) : Universidad del Norte Editorial, 2016)
More than 100 photographs rescued from the historical archives of the Compaänâia Urbanizadora El Prado and from the architectural firm Parrish & Co., accompanied by texts with relevant historical information, integrate this edition about "El Prado" neighborhood, one of the most emblematic areas of Barranquilla b25.00 a170720.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed April 30, 2018)
Keywords: El Prado (Barranquilla, Colombia) -- Buildings, structures, etc. -- Pictorial works; Architecture -- Colombia -- Barranquilla -- Pictorial works; City planning -- Colombia -- Barranquilla -- Pictorial works; Illustrated works; Electronic books